2017
DOI: 10.1186/s40409-017-0118-7
|View full text |Cite
|
Sign up to set email alerts
|

Antivenomics as a tool to improve the neutralizing capacity of the crotalic antivenom: a study with crotamine

Abstract: BackgroundSnakebite treatment requires administration of an appropriate antivenom that should contain antibodies capable of neutralizing the venom. To achieve this goal, antivenom production must start from a suitable immunization protocol and proper venom mixtures. In Brazil, antivenom against South American rattlesnake (Crotalus durissus terrificus) bites is produced by public institutions based on the guidelines defined by the regulatory agency of the Brazilian Ministry of Health, ANVISA. However, each inst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 25 publications
1
10
0
Order By: Relevance
“…Although the urine darkness, popularly described as ‘coke-like urine’, was first associated to possible hemolytic or kidney damage action of the toxins present in the rattlesnake venom, it is now recognized that in human, this is more likely determined by the myotoxic effects as rhabdomyolysis, which can eventually determine the kidney injuries [ 1 , 36 ]. All these effects have been mainly associated to the action of the neurotoxin crotoxin (phospholipase A2), also considered as the most lethal component of the rattlesnake venom (with estimated LD 50 values between 60 and 180 μg/kg of BW in mice, depending on the administration route) [ 1 , 37 , 38 ]. Crotoxin is far more toxic than crotamine, which LD 50 was described to be of about 0.07 to 6 mg/kg of BW, also depending on the administration route [ 5 , 7 , 8 , 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although the urine darkness, popularly described as ‘coke-like urine’, was first associated to possible hemolytic or kidney damage action of the toxins present in the rattlesnake venom, it is now recognized that in human, this is more likely determined by the myotoxic effects as rhabdomyolysis, which can eventually determine the kidney injuries [ 1 , 36 ]. All these effects have been mainly associated to the action of the neurotoxin crotoxin (phospholipase A2), also considered as the most lethal component of the rattlesnake venom (with estimated LD 50 values between 60 and 180 μg/kg of BW in mice, depending on the administration route) [ 1 , 37 , 38 ]. Crotoxin is far more toxic than crotamine, which LD 50 was described to be of about 0.07 to 6 mg/kg of BW, also depending on the administration route [ 5 , 7 , 8 , 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similar trend was noticed in detecting SSV venom epitopes also. As stated above, the differences in the antivenom neutralization efficiencies against HPV and SSV venom might be contributed by the antivenom production and purification protocols and the variation in the venom antigens that were used for immunizing horses while generating polyvalent antivenoms [16,17].…”
Section: Resultsmentioning
confidence: 99%
“…Boldrini-França et al reported that crotamine was not recognized by the anticrotalic sera produced by Instituto Vital-Brazil and Instituto Butantan [ 47 ], which may have led to improvements in the crotalic AV production in Brazil. Due to this lack of crotamine neutralization, Teixeira-Araújo et al established a new protocol to anticrotalic serum production by Instituto Vital-Brazil , using crotamine-positive and negative crotalic venom in the same proportion for horses immunization, which resulted in the recognition of crotamine by the new AV [ 48 ]. While in Instituto Butantan , according to the institution, a mixture of equal amounts of C. d. terrificus and C. d. collilineatus venoms collected in different regions of Brazil is used to the antivenom production.…”
Section: Discussionmentioning
confidence: 99%